2010
DOI: 10.1186/1471-2296-11-85
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the safety and efficacy of pregabalin in older patients with neuropathic pain: results from a pooled analysis of 11 clinical studies

Abstract: BackgroundOlder patients are typically underrepresented in clinical trials of medications for chronic pain. A post hoc analysis of multiple clinical studies of pregabalin in patients with painful diabetic peripheral neuropathy (DPN) or postherpetic neuralgia (PHN) was conducted to evaluate the efficacy and safety of pregabalin in older patients.MethodsData from 11 double-blind, randomized, placebo-controlled clinical studies of pregabalin in patients with DPN or PHN were pooled. Efficacy outcomes included chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 35 publications
0
69
0
Order By: Relevance
“…Frequently reported side effects include peripheral edema in 5-10% of patients and weight increase in 4-20%, but the mechanisms by which pregabalin induces these side effects have not been determined. An evaluation of the adverse effects of pregabalin in 11 clinical studies reported that central nervous system side effects included dizziness and somnolence (10%), whereas systemic side effects included peripheral edema, mouth dryness, weight gain, infection, increased appetite and constipation (26,27). Of the 19 patients in our study treated with 300 mg/day pregabalin, six (31.6%) experienced dizziness and somnolence and one (5.3%) showed pretibial edema, but none required drug discontinuation.…”
Section: Discussionmentioning
confidence: 99%
“…Frequently reported side effects include peripheral edema in 5-10% of patients and weight increase in 4-20%, but the mechanisms by which pregabalin induces these side effects have not been determined. An evaluation of the adverse effects of pregabalin in 11 clinical studies reported that central nervous system side effects included dizziness and somnolence (10%), whereas systemic side effects included peripheral edema, mouth dryness, weight gain, infection, increased appetite and constipation (26,27). Of the 19 patients in our study treated with 300 mg/day pregabalin, six (31.6%) experienced dizziness and somnolence and one (5.3%) showed pretibial edema, but none required drug discontinuation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also demonstrated the efficacy of this drug in the treatment of fibromyalgia (15), epilepsy (16), and general anxiety disorder (17). Pregabalin is usually well tolerated; however, adverse effects can include dizziness, somnolence, peripheral edema, asthenia, dry mouth, and weight gain (18). There have also been reports of heart failure (19), rashes (20), and increased liver enzyme levels (21).…”
Section: Discussionmentioning
confidence: 99%
“…It is a wellknown antiepileptic drug, exhibiting both anticonvulsant and analgesic activity in central and peripheral neuropathic pain. [130][131][132].…”
Section: Pregabalinmentioning
confidence: 99%